2008
DOI: 10.1039/b804294b
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed enantio- and diastereoselective intramolecular [2 + 2 + 2] cycloaddition of unsymmetrical dienynes

Abstract: A cationic rhodium(i)/(R)-H(8)-BINAP or (R)-Segphos complex catalyzes an intramolecular [2 + 2 + 2] cycloaddition of unsymmetrical dienynes, leading to fused tri- and tetracyclic cyclohexenes bearing two tertiary or quaternary carbon centers in high yields with high enantio- and diastereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Cationicr hodium(I)/(R)-H 8 -BINAP or (R)-SEGPHOS complexes wereu sed as the catalytic systems, achieving high yields and stereoselectivities (Scheme 21). [46] The reactions of dienynes (ene-ene-ynes) catalyzed by rhodium were reported by Shibata andc o-workers. They found that, depending on the substitution pattern,t he starting dienyne gave alternatively cyclohexadienes or strained polycyclic compounds.…”
Section: Scheme14 Asymmetric Cycloaddition Of Diynes With Norbornenementioning
confidence: 96%
See 1 more Smart Citation
“…Cationicr hodium(I)/(R)-H 8 -BINAP or (R)-SEGPHOS complexes wereu sed as the catalytic systems, achieving high yields and stereoselectivities (Scheme 21). [46] The reactions of dienynes (ene-ene-ynes) catalyzed by rhodium were reported by Shibata andc o-workers. They found that, depending on the substitution pattern,t he starting dienyne gave alternatively cyclohexadienes or strained polycyclic compounds.…”
Section: Scheme14 Asymmetric Cycloaddition Of Diynes With Norbornenementioning
confidence: 96%
“…In addition to endiynes, dienynes (ene–yne–ene) allowed the synthesis of fused tricyclic cyclohexenes bearing two tertiary or quaternary carbon centers. Cationic rhodium(I)/( R )‐H 8 ‐BINAP or ( R )‐SEGPHOS complexes were used as the catalytic systems, achieving high yields and stereoselectivities (Scheme ) …”
Section: Rhodium and Iridium Catalysismentioning
confidence: 99%
“…[35] Under these mild conditions, strained polycyclic compounds containing pairs of quaternary centers can be formed with great efficiency (Scheme 15). [36] Judicious design of the corresponding substrates allows the straightforward formation of tricyclic or tetracyclic cyclohexene derivatives also incorporating tertiary or quaternary new stereocenters (Scheme 16). [36] Judicious design of the corresponding substrates allows the straightforward formation of tricyclic or tetracyclic cyclohexene derivatives also incorporating tertiary or quaternary new stereocenters (Scheme 16).…”
Section: Dienyne Cycloadditionsmentioning
confidence: 99%
“…[1] For this asymmetric transformation, cationic rhodium(I)/axially chiral biaryl bisphosphine complexes showh igh catalytic activity and selectivity. [2] For example, our research group reported that ac ationic rhodium(I)/H 8 -binap complex is capableo fc atalyzing the regio-, diastereo-,a nd enantioselective [2+ +2+ +2] cycloaddition of 1,6-enynes [3,4] with acrylamides [5] giving chiral bicyclic cyclohexenes,p ossessing two stereogenic centers (Scheme 1a). [6] Not only acrylamides but also enamides [5a, 7] and oxabenzonorborna-dienes [8] could be employed in the rhodium-catalyzed asymmetric[ 2 + +2+ +2] cycloadditionw ith 1,6-enynes.…”
mentioning
confidence: 99%